Role of fine needle aspiration cytology in diagnosis of breast lumps - Mane, Prashant S.; Kulkarni, Aparna M.; Ramteke, Ravindra V. (International Journal of Research in Medical Sciences, 2017)
Background: Breast cancer is the most common cancer in women worldwide. Fine needle aspiration cytology is a cost effective, easy procedure in the diagnosis of breast lump. Methods: This was a one year retrospective study between January 2016 and December 2016. Needle aspiration was done in 100 patients presenting with breast lump. Histopathology correlation was done in 33 cases. Results: Fibroadenoma were most common lesions. Malignancy was reported in 13 cases. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were found to be 85%, 100%, 100%, 96.3% and 97% respectively. Conclusions: Fine needle aspiration cytology is a simple, easy, OPD based, cost effective procedure with high sensitivity, specificity and accuracy in diagnosis of breast lumps.